Bem-estar subjetivo: a influência da avaliação cognitiva e afetiva na construção da saúde mental - Medeiros, Lucélia Kelly Alencar de (2019)
The index of mental disorders presents a signifying growth, lays out the need to understand the psychosocial factors that influences the Mental Health of the subjects. The present study aims to evaluate the relationship between the Subjective Well-Being (BES) and Mental Health of the administrative technicians in education (TAE) of the Universidade Federal Rural do Semi-Árido (Ufersa), Mossoró Campus. It was based on the Model of Complete Mental Health, emphasizing the positive and negative aspects of the psychic functioning. There were 215 TAEs, with an average age of 35.21 years (± 8.13 years) and 52.1% of males. For the data collection, the Self-Reporting Questionnaire (SRQ-20), the Subjective Well-Being Scale (EBES) and the socio-biodemographic questionnaire were applied, and the analysis statistical of the data was used. The Pearson correlation test made it possible to evaluate the relationship between the socio-biodemographic characteristics of the sample and the observed measures of psychic suffering and subjective well-being. Student's t-test and ANOVA variance analysis were used to test the hypothesis that different conditions at work, as well as activities performed outside the institution, influence statistically different indexes of psychological distress and subjective well-being. Data analysis demonstrated statistically significant correlation between SRQ-20 and EBES Negative Affect subscale, while showing a negative correlation between SRQ-20 and EBES positive subscales (positive affect and life satisfaction). Analysis statistical also showed significant differences between socio-demographic variables and levels of Common Mental Disorders (CMD) and Subjective Well-Being. Regarding variables related to academic aspects and working life, there was a restricted influence on the means of psychic distress and BES, presenting a statistical correlation only between the area of APS formation and life satisfaction indexes. It was verified that the activities performed by the subjects outside the institution correlate with the levels of both psychic suffering and BES. Thus, the relationship between the indicators of Subjective Well-Being and Mental Health of the administrative technicians in education, observing the significant influence of the activities such as meeting with friends and family, physical and religious activities, as well as leisure for the prevalence of Common Mental Disorders and the happiness of their servers